Study designs and outcomes used in evaluation studies of hospital-presenting self-harm: protocol for a methodological systematic review - Eimear Ruane-McAteer; Paul Corcoran; eve griffin; John Browne; Pawel Hursztyn (BMJ Open)
Introduction Self-harm is the most common risk factor for suicide, and so those who present to hospital following self-harm provide an opportunity for targeted clinical care interventions. Observational studies evaluating such interventions may be useful in overcoming limitations of controlled trials, but study design, statistical analyses and outcomes used must be appropriate. This methodological systematic review will describe, categorise, synthesise and compare the methodological aspects of studies evaluating interventions and aspects of clinical management following hospital-presenting self-harm in both observational and experimental (ie, controlled trials or quasi-experimental studies) study designs.Methods and analysis Preferred Reporting Items for Systematic Reviews and Meta-Analysis-Protocol guidelines were followed in drafting this protocol. Search terms were developed (related to self-harm, hospital presentation and evaluation studies) and adapted for MEDLINE, PsycINFO, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials and grey literature databases. Two reviewers will independently screen 100 titles/abstracts until consensus is reached, with the remaining screened by one reviewer. Full-text screening will be conducted independently by two reviewers. Data will be extracted by one reviewer, and a second will check all data extracted. Validated risk of bias tools will be used. Data synthesis will focus on the heterogeneity of outcomes used in individual studies. Descriptive summary statistics of the data (eg, key study characteristics, type and frequency of outcomes) will be provided in categorical format, using frequencies and percentages. Outcomes will be reported separately for trials (both randomised and non-randomised trials), observational and quasi-experimental studies. Categorisation of outcomes will be guided by Cochrane Effective Practice and Organisation of Care resources for reviews of health systems interventions.Ethics and dissemination Results will be disseminated at national and international conferences and published in a peer-reviewed journal. Findings will be used to inform future studies in the area of hospital-presenting self-harm. Ethical approval is not required for this review.PROSPERO registration number CRD42020208714.